Influence of Job Satisfaction and Job Involvement of Academicians with special reference to Tamil Nadu Universities - R. , Gopinath (International Journal of Psychosocial Rehabilitation, 2020)
As the university academicians are the backbone of the higher education system, they need better guidelines, training sessions, and managerial support, and they need frequent assessments of job satisfaction and job involvement to ensure their efficiency, motivation, and commitment towards work are enhanced. Extensive studies are there about the benefits of job satisfaction and job involvement, but very few in the area of academics. In this study, the researcher attempted to study the relationship between job satisfaction and job involvement of academicians. For this purpose, 140 samples were collected from 24 universities in Tamil Nadu. The researcher used a self-administered questionnaire on job satisfaction and job involvement. Based on the analysis, the researcher found a significant and positive relationship between job satisfaction and job involvement, and job satisfaction is the major determinant of job satisfaction.